A challenging case of heparin-induced skin necrosis without thrombocytopenia. Issue 2 (March 2022) - Chidharla, Anusha; Rapoport, Eliot A.; Naffakh, Noor; Roberts, Jonathan C.
Abstract : N/A: Heparin-induced skin necrosis (HISN) is a rare complication of heparin anticoagulation. The condition occurs in various situations, including in heparin-naive and exposed individuals, in areas local or distant from the heparin injection site, and with or without frank thrombocytopenia. We present a case in which a patient treated for a pulmonary embolism with therapeutic unfractionated heparin (UFH) develops this adverse event. Symptoms were reversed with cessation of UFH and transition to bivalirudin without surgical debridement. The patient initially had anti-PF4 antibodies present but subsequent testing showed borderline antibodies and a negative serotonin release assay. After starting bivalirudin, the patient was later switched to fondaparinux without further consequences. This case illustrates the pathogenesis of HISN and provides an example of inconsistently abnormal laboratory values. Additionally, it provides two novel exposures the mRNA-1273 vaccine and the immune checkpoint inhibitor pembrolizumab that, to our knowledge, have not been previously reported.